Manajemen Pembelajaran Modern di Madrasah Diniyah Takmiliyah An Nuur Sindangkasih Kabupaten Ciamis - Sulaeman, Tatang; Al Hamdani, M. Djaswidi (Tsamratul Fikri | Jurnal Studi Islam, 2017)
Madrasah Diniyah Takmiliyah (MDT) is an institution Islamic education implemented in classical, with the aim to providing additional knowledge of Islam to the learners of Islam. Generally, learning activities at MDT have not been well managed yet. Modern Learning Management at MDTA An Nuur Cikoneng Ciamis Regency has been well implemented, ranging from learning planning, implementation of learning, to the assessment of learning. Achievement of learning at MDTA is proven to produce good graduates, both in the field of academic and morals